Diversity of Oribatids (Acari) at different land use types in Mentebah, Kapuas Hulu, West Kalimantan - Endang Sulistyorini; Rahayu Widyastuti; Sugeng Santoso (Journal of Degraded and Mining Lands Management, 2018)
Kalimantan forests are mostly managed by human. Deforestation will affect the ecosystem and species inside. Oribatids are the most abundant soil mesofauna. They have an important role in decomposition of organic matter in the soil. Here, we investigated the effect of six different land use types (i.e. primary forest, secondary forest, jungle rubber, slash and burn, young fallow and old fallow) and evaluated the effect of environmental factors on the abundance and diversity of oribatids. The oribatids were collected using transect method along 100 m with 10 sampling points with the soil depth of 0-5 cm. Oribatids were extracted using Berlese Funnel Heat Extractor. Identification of oribatids was done to family level and diversity index was determined according to Shannon's diversity index. As much as 36 families of oribatids were recorded from the site at Mentebah, Kapuas Hulu. Oribatids in the jungle rubber showed the highest abundance (592.5 individuals/m2), followed by secondary forest (317.5 individuals/m2), primary forest (287.5 individuals/m2), slash and burn (195 individuals/m2), young fallow (157.5 individuals/m2) and old fallow (142.5 individuals/m2). The value of diversity index according to Shannon Wiener (H’) ranged between 1.71-2.64 or categorized as moderate diversity values. The results of the research showed that there were strong coefficient correlation values of some families of oribatids with soil pH, C-organic, N total, C/N ratio, water content and soil temperature